Acute effect of technique modification training on 180° change of direction performance and kinematics in adolescent male soccer players - Nakamura, H.; Yamashita, D.; Nishiumi, D.; Nakaichi, N.; Hirose, N. (Frontiers in Sports and Active Living, 2025)
Introduction: Change of direction (COD) maneuvers are frequently performed during soccer games and are critical for performance. Adolescent players often display immature COD maneuvers, suggesting that COD technique modification training may be a more effective approach for adolescent athletes. This study investigated the acute effects of COD modification training on COD performance and kinematics in male adolescent soccer players.